Synthesis of 2D titanium carbide (Ti3C2) for efficient hydrogen evolution - Lau, Sherman Swee Yang (Nanyang Technological University, 2021)
Environmental pollution and energy shortage have been an issue for years and has garnered many interests to develop clean and renewable energy. While hydrogen is considered as a promising and future form of energy with high heat capacity, it is pivotal to develop an inexpensive method to produce hydrogen. Electrochemical water splitting is a method that has been intensively investigated because it only requires water which is an abundant source to produce hydrogen. However, noble metals such as platinum, performs best as electrochemical hydrogen evolution electrodes, which impedes the large-scale water splitting at a low cost. Thus, there is a need to find alternative efficient yet cost-effective electrodes for hydrogen evolution.